2020
DOI: 10.1111/1756-185x.13963
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia in patients with psoriatic arthritis: Relationship with enthesopathy, sleep, fatigue and quality of life

Abstract: Objectives To evaluate the relationship of fibromyalgia with enthesopathy, sleep, fatigue and quality of life in patients with psoriatic arthritis. Methods The psoriatic arthritis patients according to CASPAR criteria were included in the study. The diagnosis of fibromyalgia was based on 2016 ACR criteria. Demographic and clinical parameters were noted. Disease activity and enthesopathy were evaluated with Disease Activity Score‐28 (DAS‐28) and Maastricht Ankylosing Spondylitis Enthesitis Score (MASES), respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(57 reference statements)
3
12
0
Order By: Relevance
“…In this issue of the Journal 2 studies address this matter in patients with psoriatic arthritis (PsA), a condition which affects up to 1% of the population. [2][3][4] Alsawy et al identified fibromyalgia, using the 2016 modification of the 2010/11 American College of Rheumatology (ACR) criteria, 5 in 38.3% of 60 patients with PsA attending an outpatient department. 2 More PsA fibromyalgia patients were female, and more had symmetrical polyarthritis than those without fibromyalgia.…”
Section: Fibromyalgia and Psoriatic Arthritis: Partners Togethermentioning
confidence: 99%
See 4 more Smart Citations
“…In this issue of the Journal 2 studies address this matter in patients with psoriatic arthritis (PsA), a condition which affects up to 1% of the population. [2][3][4] Alsawy et al identified fibromyalgia, using the 2016 modification of the 2010/11 American College of Rheumatology (ACR) criteria, 5 in 38.3% of 60 patients with PsA attending an outpatient department. 2 More PsA fibromyalgia patients were female, and more had symmetrical polyarthritis than those without fibromyalgia.…”
Section: Fibromyalgia and Psoriatic Arthritis: Partners Togethermentioning
confidence: 99%
“…As these studies indicate, as FIQ scores increase so do the clinical and functional outcomes worsen. 3 In each of the above studies the diagnosis of fibromyalgia has been defined as either present of absent. However, fibromyalgia symptoms actually exist on a spectrum and many patients have sub-criteria symptoms that will influence their self-report of pain, fatigue, sleep and cognition.…”
Section: Fibromyalgia and Psoriatic Arthritis: Partners Togethermentioning
confidence: 99%
See 3 more Smart Citations